Predicting a responsible ecotourist behaviour: pilot study - Ibrahim, Hayati; Mariapan, Manohar; Lim, Evelyn Ai Lin; Bidin, Sheena (Human Resource Management Academic Research Society, 2022)
In sustainable ecotourism, responsible ecotourist behaviour towards purchasing local products and services is vital to alleviate poverty in local communities and help wildlife conservation. Using an extended Theory of Planned Behaviour, this study investigates the relationship between attitude, anticipated emotion, and environmental concern. This pilot study was conducted to test the reliability of the questionnaire instrument before conducting the actual research. Data collection was conducted in Penang National Park, and questionnaires were distributed face to face among the ecotourist. Samples were obtained using the purposive sampling method. Statistical Software Packages, namely SPSS version 26.0, were used to perform data analysis. The high internal consistency of items among the constructs shows that the questionnaires are reliable in conducting actual research in predicting responsible ecotourist behaviour (Cronbach Alpha value ranges from 0.883 to 0.604).